In vitro Analysis Provides New Insights into the Pharmacological Actions of Methanol Extract of Seeds of Tamarindus indica L. and its Kupchan Fractions (Bangladesh Pharmaceutical Journal, 2022)
Tamarind or Tamarindus indica L. is a multipurpose plant distributed throughout the tropics including Bangladesh. The present study was conducted to establish the preliminary antioxidant, antimicrobial, anti-inflammatory and thrombolytic activities of methanol extract of T. indica seeds along with its Kupchan fractions. To evaluate the antioxidant properties, the total phenolic content of T. indica was determined and expressed in gallic acid equivalent (GAE). Alongside, DPPH free radical scavenging assay was performed to ensure the antioxidant properties of the seeds where the methanolic crude extract revealed the maximum activity having IC50 value of 9.43 μg/ml. In the antimicrobial assay by disk diffusion method, only non-polar fractions of the extract showed mild antimicrobial activity against the test organisms tested while the polar crude methanol extract exhibited the maximum inhibition (58.16%, p < 0.001) of hypotonic solution-induced erythrocyte rupture in anti-inflammatory investigation among all the partitionates. During evaluation of thrombolytic activity in terms of percent of clot lysis, the methanol soluble fraction exhibited the highest percent of thrombolysis (23.5%) as compared to the reference standard, streptokinase (64.25%). The findings of the current study rationalize some of the traditional uses of T. indica and preliminarily ascertain its bioactive potential, which may act as a base for phytochemical and mechanism-based pharmacological studies of the plant in future.Bangladesh Pharmaceutical Journal 25(1): 9-15, 2022 (January)